The Roles of Non-coding RNA in the Development and Regeneration of Hair Follicles: Current Status and Further Perspectives - Yang, Min; Weng, Tingting; Zhang, Wei; Zhang, Manjia; He, Xiaojie; Han, Chunmao; Wang, Xingang (Frontiers in Cell and Developmental Biology, 2021)
Alopecia is a common problem that affects almost every age group and is considered to be an issue for cosmetic or psychiatric reasons. The loss of hair follicles (HFs) and hair caused by alopecia impairs self-esteem, thermoregulation, tactile sensation and protection from ultraviolet light. One strategy to solve this problem is HF regeneration. Many signalling pathways and molecules participate in the morphology and regeneration of HF, such as Wnt/β-catenin, Sonic hedgehog, bone morphogenetic protein and Notch. Non-coding RNAs (ncRNAs), especially microRNAs and long ncRNAs, have significant modulatory roles in HF development and regeneration via regulation of these signalling pathways. This review provides a comprehensive overview of the status and future prospects of ncRNAs in HF regeneration and could prompt novel ncRNA-based therapeutic strategies.